Determination of plane strain fracture toughness for AZ61 Magnesium alloy - M. A. M., Daud; Mohd. Zaidi, Omar; Syarif Junaidi, S Djalil; Zainuddin, Sajuri (Universiti Malaysia Perlis, 2010)
Organized by School of Materials Engineering & Sustainable Engineering Research Cluster, 1st - 2nd December 2009 at Putra Brasmana Hotel, Kuala Perlis, Perlis.